Building an Optimal Portfolio on Indonesia Sharia Stock Index (ISSI) - Hadiyoso, Asto; Firdaus, Muhammad; Sasongko, Hendro (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2016)
Indonesian economy is particularly susceptible to capital outflow and net sell position due to the relatively high share of foreign ownership in the stock and government debt market. One of the efforts to reduce the vulnerability is to increase the involvement of public participation in the capital market. The purpose of this study was to establish the optimal portfolio generated from stocks listed on Indonesia Sharia Stock Index (ISSI) and measure its performance in order to determine its potential as an instrument for the major community to invest in the stock market. Calculations using single index model approach, daily stock price data and inflation rate as a proxy of the risk free rate, produce the optimal portofolio composed of forty three stocks with preferable yield and risk than the markets (Jakarta Composite Index). The number of stocks and the value of risk which is smaller than the market risk indicate that the portfolio are well diversified. The results of the performance test using Jensen’s Alpha method shows that the portfolio are able to outperform the market, JII, and ISSI.